2010
DOI: 10.1016/j.jcin.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Embolic Cerebral Insults After Transapical Aortic Valve Implantation Detected by Magnetic Resonance Imaging

Abstract: New embolic ischemic cerebral insults are detected in 68% of patients after transapical valve implantation. Clinical symptoms are rare and usually transitory. Larger trials will need to establish the clinical significance of asymptomatic ischemic lesions as well as the rate of ischemic events in patients undergoing transfemoral valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(56 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…2,[13][14][15] Brain MRI studies have established subclinical procedure-related cerebral diffusion-weighted imaging abnormalities in up to 80% of cases after TAVR, approximately double the rate that has been reported after surgical aortic valve replacement. 6,7,[14][15][16][17][18] Independent neurological assessment of TAVR patients is not routinely performed, and, thus, some subtle neurological defects may go unrecognized; however, many emboli likely travel to clinically silent areas of the brain. These new cerebrovascular embolic events may not be trivial, because subclinical microinfarctions may be associated with neurocognitive decline and premature dementia.…”
Section: Discussionmentioning
confidence: 99%
“…2,[13][14][15] Brain MRI studies have established subclinical procedure-related cerebral diffusion-weighted imaging abnormalities in up to 80% of cases after TAVR, approximately double the rate that has been reported after surgical aortic valve replacement. 6,7,[14][15][16][17][18] Independent neurological assessment of TAVR patients is not routinely performed, and, thus, some subtle neurological defects may go unrecognized; however, many emboli likely travel to clinically silent areas of the brain. These new cerebrovascular embolic events may not be trivial, because subclinical microinfarctions may be associated with neurocognitive decline and premature dementia.…”
Section: Discussionmentioning
confidence: 99%
“…42 devices and approaches ( Figure 5). 35,[43][44][45][46][47] Analysis of diffusionweighted (DW) MRI studies performed pre-and post-TAVI includes a cumulative total of only 222 patients. TA-TAVI with ES was performed in 68 of these patients, with 52 (76.5%) having newly identified ischemic lesions on MRI postprocedure, and 2 (2.9%) with clinically manifest CVEs.…”
Section: Diffusion-weighted Mrimentioning
confidence: 99%
“…43 Although early studies using DW-MRI supported this, 43,47 the association has not been confirmed by more recent studies. 35,[44][45][46] Similarly, although findings have been inconsistent, there is the suggestion of increased vulnerability of the anterior circulation in comparison with the posterior circulation, with a preponderance for new ischemic lesions in the middle cerebral artery territories. 35,44,45 Not surprisingly, the incidence and volume of preoperative silent ischemic lesions (present in 70% of patients) predicted the occurrence of new postoperative lesions.…”
Section: Diffusion-weighted Mrimentioning
confidence: 99%
“…Furthermore, the average 30-day mortality in TAVR patients with post-procedural stroke was more than 3.5-fold higher than in non-stroke patients (25.5 vs. 6.9) [3]. In addition to the clinically apparent ischemic brain lesions, several cerebral magnetic resonance imaging studies have shown a very high (58-91 %) incidence of new ischemic lesions after TAVR, regardless of the transcatheter valve type and approach (Table 1) [4][5][6][7][8][9]. These small, usually asymptomatic, DWI lesions are most probably caused by micro-embolic particles arising during the valve implantation procedure.…”
Section: Introductionmentioning
confidence: 99%